Modeling of processes of friction and wear in tribosystems in the conditions boundary lubrication. Part 1. Calculating the speed of dissipation in tribosystem - Войтов, В.А.; Захарченко, М.Б. (Problems of Tribology, 2015)
Vojtov V.A., Zaharchenko M.B. Modeling of processes of friction and wear in tribosystems in the conditions boundary lubrication. Part 1. Calculating the speed of dissipation in tribosystem. The paper presents the theoretical research to substantiate the techniques of modeling processes of friction and wear in tribosystems in the conditions boundary lubrication. The technique of modeling the behavior of the actual contact patch and a mathematical model of the speed of dissipation in tribosystem. The theoretical dependence of the change of these characteristics of the input parameters.